Feminism's Empire - Eichner, Carolyn Jeanne, 1961- (Book collections on Project MUSE., 2022)
Feminism's Empire investigates the complex relationships between imperialisms and feminisms in the late-nineteenth century and demonstrates the challenge of conceptualizing "pro-imperialist" and "anti-imperialist" as binary positions. By intellectually and spatially tracing the era's first French feminists' engagement with empire, Carolyn J. Eichner explores how feminists opposed--yet employed-- approaches to empire in writing, speaking, and publishing. In their differing ways, they ultimately tied forms of imperialism to gender liberation. Among the era's first anti-imperialists, French feminists were enmeshed in the hierarchies and epistemologies of empire. They likened their gender-based marginalization to imperialist oppressions. Imperialism and colonialism's gendered and sexualized racial hierarchies established categories of inclusion versus exclusion that rested in both universalism and ideas of "nature" that presented colonized people theoretical, yet impossible, paths to integration. Feminists faced similar barriers to full incorporation due to the gendered contradictions inherent in universalism. The system presumed citizenship as male and thus positioned women as outsiders. Feminism's Empire connects this critical struggle to hierarchical power shifts in racial and national status that created uneasy linkages between French feminists and imperial authorities